1998
DOI: 10.1038/sj.onc.1202120
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of minisatellite and microsatellite instability in radiation-induced post-Chernobyl pediatric thyroid carcinomas

Abstract: Exposure to ionizing radiation induces di erent forms of genomic instability in cultured cells and experimental animals. A higher rate of germline mutations at human hypervariable minisatellite loci was reported in children born from parents exposed to radiation after Chernobyl, implicating genome destabilization as a possible mechanism responsible for late radiation e ects in humans. To test if radiation-induced carcinogenesis in the thyroid gland may be associated with somatic minisatellite instability or mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 20 publications
1
23
0
1
Order By: Relevance
“…Moreover, a recent study suggested that p53 gene point mutations may play a pathogenic role in some radiation-induced well di erentiated thyroid cancers, explaining the aggressiveness of some of these tumors (Fogelfeld et al, 1996). In contrast with the data from Challeton et al (1995), in tumors arising in children after the Chernobyl accident Nikiforov et al (1996) observed ras point mutations in 1/1 follicular carcinoma and in 3/7 follicular adenomas, but not in the 33 papillary carcinomas studied. These authors concluded that ras does not appear to be important in the development of the Chernobyl papillary carcinomas.…”
Section: Introductionmentioning
confidence: 67%
“…Moreover, a recent study suggested that p53 gene point mutations may play a pathogenic role in some radiation-induced well di erentiated thyroid cancers, explaining the aggressiveness of some of these tumors (Fogelfeld et al, 1996). In contrast with the data from Challeton et al (1995), in tumors arising in children after the Chernobyl accident Nikiforov et al (1996) observed ras point mutations in 1/1 follicular carcinoma and in 3/7 follicular adenomas, but not in the 33 papillary carcinomas studied. These authors concluded that ras does not appear to be important in the development of the Chernobyl papillary carcinomas.…”
Section: Introductionmentioning
confidence: 67%
“…The panel of TP53 mutations is uncommon TP53 status has been described in several series of radiation-induced sarcomas and carcinomas (Behrens et al, 2000;Brachman et al, 1991;Brat et al, 1999;De Benedetti et al, 1996;Fogelfeld et al, 1996;Gamble et al, 1999;Nakanishi et al, 1998;Nikiforov et al, 1996;Tada et al, 1997). In these series, the rates of mutations ranged from 0 to 100%, which makes any ®rm conclusion impossible.…”
Section: Discussionmentioning
confidence: 99%
“…First, they are aggressive cancers, almost all are of papillary type and often invade the neighboring tissues (Williams, 1994). Second, genetic analysis revealed a relatively high prevalence of ret/PTC (approximately 60%) (Fugazzola et al, 1995;Santoro et al, 1996), whereas very few point mutations of p53 and ras genes were detected (Nikiforov et al, 1996). These ®ndings suggest that thyroid tumors occurring around Chernobyl were caused by exposure to ionizing radiation known to cause double strand breaks of genomic DNA.…”
Section: Discussionmentioning
confidence: 99%